Environmental Evidence - Pullin, Andrew; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Environmental Evidence publishes objective scientific evidence to inform policy and practice by publishing evidence syntheses (including meta-analyses) relevant to environmental management. The journal is managed by the Collaboration for Environmental Evidence (CEE) and facilitates rapid publication of rigorous evidence syntheses, in the form of Systematic Reviews, Rapid Reviews and Systematic Maps, conducted to CEE Guidelines and Standards. Our scope covers the realm of environmental science and management broadly recognizing the interdisciplinary nature of the field which spans the natural and social sciences and extends from identifying environmental threats and problems, evaluating environmental interventions, assessing human impacts on the environment, to generating and testing environmental solutions. Subjects include but are not limited to climate change, natural resource management, forestry, fisheries, biodiversity conservation, invasive species, ecosystem services, environmental impacts on human wellbeing, sustainable energy, water security, agriculture, soil management, food security, sustainable food production and consumption, One Health, waste and wastewater management, pollution, clean growth, ecotoxicology, environmental justice, environmental governance, environmental legislation and environmental education. We recognize that traditional evidence synthesis and decision making has excluded Indigenous knowledge systems and other ways of knowing and welcome contributions that explore approaches for doing such work in a more inclusive manner. Despite the large and rapidly increasing amounts of primary environmental research, the potential of the data to address questions of concern to policy makers and managers has not been fully realised. This journal and CEE promotes and facilitates the conduct and use of evidence syntheses and seeks to make evidence more accessible to all through open access publishing of papers on all aspects of environmental science and management. To this end we also publish the following paper types. Objective use of scientific evidence to inform policy or practice is a major aim and to that end the Journal also publishes methodology papers and encourages submissions that promise advances in the field of evidence synthesis, including methodological contributions to advance co-design processes used in syntheses, communication of findings or evidence uptake. We also welcome empirical natural or social science studies that analyse various aspects of evidence generation and use. Discussion of wider issues surrounding the production and communication of evidence syntheses are welcome in the form of commentary articles. Evidence in Action articles should involve a discussion on the impact of evidence-based practice on environmental managers, of evidence synthesis on policy making, or a discussion of developments at the science-policy interface. Proposals for Special Series of papers on a specific theme are welcomed and you should contact the Editor-in-Chief at an early stage.
Keywords: Environmental management; Biotic communities; Environmental Law; Environmental policy; Forestry; Environmental Management; Ecosystems; Environmental Law; Environmental Policy; Forestry